Transfer Pricing Determinants in Indonesian Listed Firms - Adam Muhamad Satria; Suparna Wijaya; Ferry Irawan (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study examines the effects of free-float shares, capital structure, and tunneling incentives on transfer pricing. The free-float share is a novelty of this study. Research Methodology: This study employs a quantitative methodology based on secondary data obtained from the annual reports of companies listed on the Indonesian Stock Exchange between 2023 and 2024. Sample selection was conducted using purposive sampling, and the empirical analysis was performed using panel data regression with Moderated Regression Analysis (MRA) in Stata. Results: The results reveal that free-float shares and capital structure are negatively associated with transfer pricing practices, whereas tunneling incentives exhibit a positive relationship. In addition, foreign ownership attenuates the effect of capital structure on transfer pricing. However, it does not play a moderating role in the relationship between free-float shares and transfer pricing, or in the relationship between tunneling incentives and transfer pricing. Conclusions: Free-float shares and tunneling reduce transfer pricing practices, whereas tunneling incentives increase them. Foreign ownership weakens the leverage effect but does not moderate the influence of free-float shares or tunneling incentives. Limitations: The firms from all industry sectors without distinguishing industry-specific characteristics, such as intangible asset intensity, cost structures, and cross-border transaction exposure. In addition, the linear regression model may not fully capture potential nonlinear relationships or endogeneity issues. Contributions: This study contributes to the transfer pricing literature by introducing free-float shares as a novelty determinant and by clarifying the conditional role of foreign ownership within a moderating framework.